A comparative study on wear behaviour of Cr/Mo surface modified grey cast iron. (August 2018) - Zulhishamuddin, A.R.; Aqida, S.N.; Mohd Rashidi, M.
Highlights: Grey cast iron surface was modified using laser cladding with addition of Cr and Mo powders. Effect of powder composition and laser parameter on dendrite structure formation was discussed. Clad layer exhibited maximum hardness properties of 945.5 HV0.1 . Addition of Cr-Mo powder mixture enhanced wear rate of clad layer up to 98%. Abstract: This paper presents laser cladding of grey cast iron with addition of Cr and Mo powder for enhanced wear properties. The laser cladding process was conducted using a Nd:YAG laser system. Sliding wear test were carried out on a linear reciprocating wear testing machine to analyse the wear rate during dry sliding. Based on the metallographic study, graphite phase was eliminated from the clad zone and formed small dendrite structure with fine particles. This phenomenon increased the hardness properties of the cladding surface with a maximum hardness of 945.5 HV0.1 . Meanwhile, the wear resistance of cladding surface was improved relative to the as-received grey cast iron with weight loss reduction of more than 96 percent. When Cr-Mo mixture was added, the worn surfaces were moderately smooth with only slight scratches and minimal adhesive attribute because of the formation of carbide phase. The improvement of the grey cast iron surface was due to the change of chemical composition and presence of the hard phase, M2 C, M3 C2 and M23 C6 produced by laser cladding.